(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In this study, the impact of CO2 laser engraving and scanning on various types of wood before and after thermal treatment is investigated. An infrared CO2 laser with a wavelength of 10640 nm is used in the study for engraving various wood samples before and after thermal treatment at a specific processing temperature of 214°C. All samples had a similar moisture content - approximately 8%. The engraving depth and width were measured for each wood sample. The findings reveal that thermal pre-treatment exert a discernible influence on the efficacy of laser engraving, and the engraving depth is notably influenced by the particular wood species involved. Consequently, the study offers a platform for assessing the optimization of laser engraving parameters applicable to different wood types and thermally modified wood, thereby facilitating the enhancement of product quality through judicious parameter selection.